IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA PEMBELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA DI KELAS IV SD - Thera Dies Yunizha; Faizal Chan; Issaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Culturally Responsive Teaching (CRT) approach in the teaching of Natural and Social Sciences (IPAS) on the topic